Acrylate copolymer with different glass transition temperatures, bone cement and preparation method and application thereof
By introducing organic monomer copolymers with different glass transition temperatures into polymethyl methacrylate, acrylate copolymers and bone cement suitable for a variety of medical applications were prepared, and the mechanical properties of PMMA materials in different application scenarios were solved. The problem of insufficient achieves the adaptation to the strength and toughness requirements of different parts and simplifies the preparation process.
Patent Information
- Application Number
- CN202411399262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-27
AI Technical Summary
The mechanical properties of existing polymethyl methacrylate (PMMA) materials cannot meet the diverse needs in different medical application scenarios and cannot adapt to the strength and toughness requirements of different parts.
By copolymerizing methyl methacrylate with organic monomers or homopolymers with different glass transition temperatures, acrylate copolymers with different glass transition temperatures are prepared, and a new type of bone cement is formed by combining powders and liquids. in different medical scenarios.
Acrylate copolymers with adjustable mechanical properties are achieved with different glass transition temperatures and adjustable mechanical properties. They are suitable for osteoporotic fractures, joint replacement and other scenarios, meet the mechanical properties needs of different parts of the human body, simplify the preparation process and reduce costs. .
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to an acrylic copolymer with different glass transition temperatures, bone cement, and a preparation method and application thereof. Background Art
[0002] With the progress of social development and the improvement of people's living standards, medical devices are also constantly developing and improving. Polymethyl methacrylate (PMMA) is an important material for many medical procedures. Because it is easy to dye, can be quickly formed, and has excellent biocompatibility, it is mainly used in the medical field to make dental base materials and bone repair materials. However, at present, PMMA materials are severely homogenized in different application scenarios, that is, the performance, characteristics or application methods in different application scenarios are gradually becoming consistent, which cannot meet its use requirements under different strength and toughness conditions. Summary of the invention
[0003] In view of the above technical problems, the present invention provides an acrylic copolymer with different glass transition temperatures, bone cement, and a preparation method and application thereof, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.
[0004] As a first aspect of the present invention, there is provided an acrylic copolymer having different glass transition temperatures, which is obtained by copolymerizing methyl methacrylate or its homopolymer and an organic monomer or its homopolymer; Among them, the organic monomer or its homopolymer includes one or two of styrene, polystyrene, methyl acrylate, polymethyl acrylate, ethyl methacrylate, polyethyl methacrylate, 2-ethylhexyl acrylate, poly2-ethylhexyl acrylate, and organosiloxane; the glass transition temperature of the acrylate copolymer is -60~140℃.
[0005] As a second aspect of the present invention, there is provided a method for preparing the above-mentioned acrylic acid ester copolymer, comprising: Methyl methacrylate or its homopolymer and organic monomer or its homopolymer are added to a dispersant aqueous solution, and an initiator is added to perform a polymerization reaction in an inert gas under heating, and then a aging reaction is performed to obtain an acrylic ester copolymer.
[0006] As a third aspect of the present invention, there is provided an application of the above-mentioned acrylic acid ester copolymer, comprising at least one of the following: Application in the preparation of bone cement for the treatment of osteoporotic fractures; application as bone cement for fixing prostheses in joint replacement surgery; application as orthodontic bases or denture bases in dental treatment; application as dental models in dental treatment; application as filling materials for plastic surgery or restoration in the field of medical aesthetics.
[0007] As a fourth aspect of the present invention, there is provided a bone cement comprising powder and liquid, wherein the amount of powder added to a unit volume of liquid is 1.5-2.5 g; Wherein, in terms of mass percentage, the above powder includes: The above-mentioned acrylic acid ester copolymer 69.5-89.99%, Developer 10-30%, Benzoyl peroxide 0.01-0.5%; In terms of mass percentage, the above liquids include: Acrylate monomers 94.5-99.98%, N,N-dimethyl-p-toluidine 0.01-5%, Inhibitor 0.01-0.5%.
[0008] As a fifth aspect of the present invention, there is provided a method for preparing the above-mentioned bone cement, comprising: The acrylic copolymer, developer and benzoyl peroxide are mixed to obtain bone cement powder; Mixing acrylate monomers, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain liquid bone cement; adding the powder into the liquid and mixing to obtain bone cement; Among them, the amount of powder added per unit volume of liquid is 1.5-2.5g.
[0009] As a sixth aspect of the present invention, there is provided an application of the above-mentioned bone cement, comprising at least one of the following: Application in the treatment of osteoporotic fractures; Application in the fixation material of prosthesis in joint replacement.
[0010] Based on the above technical solutions, the present invention provides an acrylic copolymer with different glass transition temperatures, bone cement, and a preparation method and application thereof, which have at least one of the following beneficial effects.
[0011] (1) In the embodiments of the present invention, polymethyl methacrylate is a material with excellent biocompatibility, mechanical properties and processability, and is widely used in the medical field, but the mechanical properties of pure polymethyl methacrylate cannot meet the needs of different medical scenarios. Therefore, the present invention proposes an acrylate copolymer obtained by copolymerizing methyl methacrylate or its homopolymer with an organic monomer or its homopolymer, and by introducing organic monomers or their homopolymer segments with different glass transition temperatures into polymethyl methacrylate or its homopolymer, a series of acrylate copolymers with different glass transition temperatures and adjustable mechanical properties are obtained, which are suitable for different medical scenarios, such as: treatment of osteoporotic fractures in orthopedics, fixation of prostheses in joint replacement surgery; production of orthodontic bases and denture bases in dentistry, etc.
[0012] (2) In the embodiments of the present invention, acrylate copolymers with different glass transition temperatures are obtained by copolymerizing methyl methacrylate or its homopolymer with an organic monomer or its homopolymer. The preparation method is simple, low-cost, controllable experimental conditions, and a short synthesis cycle. By utilizing the difference in glass transition temperatures of different organic monomers or their homopolymers, a series of acrylate copolymers with different glass transition temperatures and adjustable mechanical properties are synthesized. The acrylate copolymers have different strengths and toughnesses, which can be used to meet the strength and toughness requirements of different parts.
[0013] (3) In the embodiments of the present invention, polymethyl methacrylate bone cement is a biomaterial used to fill the gap between bone and implant or bone cavity and has self-setting properties. It is increasingly popular in minimally invasive surgery, but currently acrylate bone cement cannot meet the mechanical property requirements of different parts of the human body. Therefore, the present invention proposes a new type of bone cement composed of acrylate copolymers with different glass transition temperatures as powders and liquids, wherein the acrylate copolymers with different glass transition temperatures make the obtained bone cement have different strengths and toughness, which can be adapted to different parts of the human body, such as: treatment of osteoporotic fractures in orthopedics, fixation of prostheses in joint replacement surgery, etc.
[0014] (4) In the embodiment of the present invention, the powder raw material and the liquid raw material are mixed separately and set aside. When they are used, the powder and the liquid are mixed evenly in proportion, and a self-polymerization reaction occurs between the powder and the liquid. After the reaction is completed, bone cements with different strengths and moduli can be obtained. The preparation method is simple and takes a short time. It can be applied to different parts of the human body or other commercial applications. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0016] Polymethyl methacrylate (PMMA) is widely used in the field of medical devices and has excellent biocompatibility, mechanical properties and processability. The particle size of PMMA microsphere polymer is 10~70μm, and the weight-average molecular weight is 400,000~1 million. After mixing with monomers and initiators, it can initiate self-polymerization reaction, which makes PMMA applicable to various scenarios that require shaping and setting, and has high flexibility. The application of heat-cured PMMA as a denture base material has pioneered the application of PMMA materials in dentistry. Later, PMMA bone cement was used as a fixation material for femoral stem prostheses, making the application of PMMA bone cement one of the iconic key technologies in modern artificial joint surgery. However, the mechanical properties of pure PMMA materials have certain defects and cannot meet the requirements of mechanical properties in different medical scenarios. In recent years, research on PMMA modification has been developing continuously, but most of them focus on modification of biocompatibility and strength, by introducing rigid particles into PMMA to increase PMMA strength, or adding materials such as hydroxyapatite into PMMA to improve its biological activity. There are few studies on the effect of glass transition temperature on material strength and toughness, and few products have been developed for this purpose. PMMA products in clinical use should have personalized toughness and strength conditions in different application scenarios. For example, the material strength for vertebroplasty should be close to 20MPa and the modulus should be less than 500MPa, while the material strength for joint replacement should be greater than 60MPa and the modulus should be greater than 1000MPa.
[0017] Based on this, the present invention provides an acrylate copolymer with different glass transition temperatures, bone cement, and a preparation method and application thereof. By introducing organic monomers or homopolymers thereof with different glass transition temperatures, methyl methacrylate or its homopolymer is copolymerized with the organic monomer or its homopolymer, and a series of acrylate copolymers with different glass transition temperatures and adjustable mechanical properties are synthesized. When introducing organic monomers or their homopolymers, the following conditions must be met: copolymerization with methyl methacrylate or its homopolymer, low toxicity, and different glass transition temperatures. In the present invention, the methyl methacrylate-styrene copolymer improves the strength and stiffness of pure PMMA materials, and the methyl methacrylate-methyl acrylate copolymer, the methyl methacrylate-ethyl methacrylate copolymer, the methyl methacrylate-acrylic acid-2-ethylhexyl ester copolymer, and the methyl methacrylate-organosiloxane copolymer reduce the strength and stiffness of pure PMMA materials to varying degrees and improve toughness, thereby providing a series of acrylate copolymers suitable for different medical scenarios.
[0018] Specifically, as a first aspect of the present invention, there is provided an acrylic copolymer having different glass transition temperatures, which is obtained by copolymerizing methyl methacrylate or a homopolymer thereof with an organic monomer or a homopolymer thereof; Among them, the organic monomer or its homopolymer includes one or two of styrene, polystyrene, methyl acrylate, polymethyl acrylate, ethyl methacrylate, polyethyl methacrylate, 2-ethylhexyl acrylate, poly2-ethylhexyl acrylate, and organosiloxane; the glass transition temperature of the acrylate copolymer is -60~140℃.
[0019] In the embodiment of the present invention, polymethyl methacrylate is a material with excellent biocompatibility, mechanical properties and processability, and is widely used in the medical field, but the mechanical properties of pure polymethyl methacrylate cannot meet the needs of different medical scenarios. Therefore, the present invention proposes an acrylate copolymer obtained by copolymerizing methyl methacrylate or its homopolymer with an organic monomer or its homopolymer, and by introducing organic monomers or their homopolymer segments with different glass transition temperatures into polymethyl methacrylate or homopolymer, a series of acrylate copolymers with different glass transition temperatures and adjustable mechanical properties are obtained, which are suitable for different medical scenarios.
[0020] In some embodiments, the glass transition temperature of methyl methacrylate is 105°C, the glass transition temperature of styrene is 100°C, the glass transition temperature of ethyl methacrylate is 65°C, the glass transition temperature of methyl acrylate is 9°C, the glass transition temperature of 2-ethylhexyl acrylate is -70°C, and the glass transition temperature of organosiloxane is -125°C. Based on this, the glass transition temperature of methyl methacrylate-styrene copolymer in the acrylic ester copolymer prepared by the present invention is 100~140°C, the glass transition temperature of methyl methacrylate-ethyl methacrylate copolymer is 60~100°C, the glass transition temperature of methyl methacrylate-methyl acrylate copolymer is 40~80°C, the glass transition temperature of methyl methacrylate-2-ethylhexyl acrylate copolymer is 0~60°C, and the glass transition temperature of methyl methacrylate-organosiloxane copolymer is -60~60°C.
[0021] In other embodiments, two organic monomers or their homopolymers can be selected to make the glass transition temperature more controllable, for example: methyl methacrylate, styrene, and ethyl methacrylate are copolymerized to obtain methyl methacrylate-styrene-ethyl methacrylate copolymer; methyl methacrylate, methyl acrylate, and 2-ethylhexyl acrylate are copolymerized to obtain methyl methacrylate-methyl acrylate-2-ethylhexyl acrylate copolymer. In addition to the above-mentioned acrylic copolymers, other different combinations can also be adjusted according to the user.
[0022] As a second aspect of the present invention, there is provided a method for preparing the above-mentioned acrylic acid ester copolymer, comprising: Methyl methacrylate or its homopolymer and organic monomer or its homopolymer are added to a dispersant aqueous solution, and an initiator is added to perform a polymerization reaction in an inert gas under heating, and then a aging reaction is performed to obtain an acrylic ester copolymer.
[0023] In an embodiment of the present invention, acrylate copolymers with different glass transition temperatures are obtained by copolymerizing methyl methacrylate or its homopolymer with an organic monomer or its homopolymer. The preparation method is simple, low-cost, controllable experimental conditions, and a short synthesis cycle. By utilizing the difference in glass transition temperatures of different organic monomers or their homopolymers, a series of acrylate copolymers with different glass transition temperatures and adjustable mechanical properties are synthesized. The acrylate copolymers have different strengths and toughnesses, which can be used to adapt to the strength and toughness requirements of different parts.
[0024] According to an embodiment of the present invention, the dispersant includes at least one of polyvinyl alcohol, tricalcium phosphate, and hydroxy calcium phosphate; the initiator includes any one of azobisisobutyronitrile, benzoyl peroxide, and ammonium persulfate. The acrylic copolymer is obtained by suspension polymerization of methyl methacrylate or its homopolymer and organic monomer or its homopolymer. During the polymerization process, the dispersant can adhere to or adsorb on the surface of the droplets formed by methyl methacrylate or its homopolymer and the organic monomer or its homopolymer to form a protective layer, effectively preventing the droplets from sticking, maintaining the stability of the suspension system, and also helping to reduce the interfacial tension between the monomer and the water phase, promoting the uniform dispersion of the monomer in water, and forming finer droplets, thereby improving the polymerization efficiency and the quality of the copolymer. Among them, in addition to water, the dispersant can also be dissolved in other solvents that are immiscible with the raw materials and non-toxic to obtain a dispersant solution.
[0025] According to an embodiment of the present invention, the temperature of the polymerization reaction is 60-80°C, and the time of the polymerization reaction is 0.5-3.5h; the temperature of the aging reaction is 80-100°C, and the time of the aging reaction is 1-3h. After the polymerization reaction is completed, the aging reaction is carried out to further react the residual monomers and the groups that have not reacted completely in the polymerization reaction, thereby improving the conversion rate of the copolymer and making the copolymer more complete and stable. Ripening can accelerate the reaction rate of the residual organic monomers and make the reaction more complete. However, too high a aging temperature can lead to the breakage of the copolymer molecular chain and the occurrence of side reactions, thereby affecting the performance of the copolymer. Low-temperature aging can avoid the negative effects of high temperature, but the aging rate is slow and it takes longer to achieve the ideal aging effect. The length of the aging time directly affects the performance of the copolymer. Too short a aging time will lead to incomplete copolymer reaction and decreased performance; while too long a aging time will increase production costs and energy consumption.
[0026] According to an embodiment of the present invention, the mass ratio of methyl methacrylate or its homopolymer to the organic monomer or its homopolymer is 1 to 9: 1, so as to ensure that methyl methacrylate or its homopolymer is the main unit in the acrylic copolymer. The mass ratio of the total mass of methyl methacrylate or its homopolymer to the organic monomer or its homopolymer to the dispersant aqueous solution is controlled to control the particle size of the acrylic copolymer. The larger the mass of the dispersant aqueous solution, the smaller the particle size of the acrylic copolymer. Preferably, the mass ratio of the total mass of methyl methacrylate or its homopolymer to the organic monomer or its homopolymer to the dispersant aqueous solution is 1: 19 to 3: 7. When the dispersant concentration is appropriate, a protective layer can be effectively formed on the surface of the droplets to reduce the interaction force between the droplets, thereby preventing them from sticking to each other or agglomerating into blocks. In general, as the dispersant concentration increases, the copolymer particle size will decrease and the particle size distribution will become more uniform. However, too high a dispersant concentration will cause the droplets to be too small, which will affect the performance of the copolymer. Preferably, the dispersant concentration is 0.005 to 0.02 g / mL. The amount of initiator added has a significant effect on the polymerization reaction. An appropriate amount of initiator can accelerate the polymerization rate, but too much will lead to excessive reaction, making the copolymer particles difficult to disperse and easy to agglomerate, affecting the uniformity and yield of the copolymer. At the same time, too much initiator will also make the molecular weight distribution of the copolymer wider, increase the degree of branching, and affect the performance of the copolymer. Preferably, the mass of the initiator is 1-10wt% of the total mass of methyl methacrylate or its homopolymer and the organic monomer or its homopolymer.
[0027] In some embodiments of the present invention, a polymerization inhibitor is often added to the purchased methyl methacrylate to prevent the methyl methacrylate from self-polymerization and to prolong the storage period. Therefore, the added polymerization inhibitor can be removed by alkali washing before use. Specifically, the following operation can be performed: the methyl methacrylate is extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution and then washed with deionized water until neutral, and dried to remove the polymerization inhibitor in the methyl methacrylate.
[0028] Specifically, the preparation method of the acrylic copolymer includes: dissolving the dispersant in deionized water, stirring for 0.5h in a constant temperature water bath at 60-80°C, activating the dispersant, and obtaining a dispersant aqueous solution. Methyl methacrylate or its homopolymer and organic monomer or its homopolymer are added to the dispersant aqueous solution, an initiator is added, the stirring speed is 800rpm / min, and the temperature is 60-80°C under nitrogen protection for 0.5-3.5h. After the reaction is completed, it is aged at 80-100°C for 1-3h to terminate the reaction, and the supernatant is removed after standing and settling, and the dispersant is removed by washing with hydrochloric acid, and washed with distilled water until neutral, and vacuum dried after filtration, and sieved to obtain an acrylic copolymer.
[0029] As a third aspect of the present invention, there is provided an application of the above-mentioned acrylic acid ester copolymer, comprising at least one of the following: Application in the preparation of bone cement for the treatment of osteoporotic fractures; application as bone cement for fixing prostheses in joint replacement surgery; application as orthodontic bases or denture bases in dental treatment; application as dental models in dental treatment; application as filling materials for plastic surgery or restoration in the field of medical aesthetics.
[0030] In some embodiments, acrylic copolymers can be used to make orthodontic bases or denture bases, and the preparation method includes: uniformly mixing acrylic copolymers with denture water, filling the mixture into a mold when it enters the dough stage, heating and curing the mold, and the resulting material is the orthodontic base or denture base.
[0031] In other embodiments, the application of acrylic copolymers in medical aesthetics is mainly in the permanent filling of nasolabial wrinkles, external nose volume and shape, mandibular contour of patients with mild to moderate mandibular retrusion, mid-face volume loss or contour defects, correction of structural defects such as lip asymmetry or contour deformity and lip volume defect, frontal dynamic wrinkles, perioral wrinkles, mandibular arc, temporal, infraorbital depression, etc. Acrylic copolymers can be used to make plastic or repair materials, and the preparation method thereof includes: mixing acrylic copolymers with collagen, phosphate buffer, sodium chloride solution, and lidocaine hydrochloride to obtain plastic or repair materials.
[0032] Specifically, the preparation method of the plastic surgery or repair material includes: fully mixing 20wt% methyl methacrylate-ethyl methacrylate copolymer or methyl methacrylate-2-ethylhexyl acrylate copolymer, 3.5% bovine collagen or sodium hyaluronate, 2.7% phosphate buffer, 0.9% sodium chloride solution, 0.3% lidocaine hydrochloride and 72.6% water to obtain the plastic surgery or repair material.
[0033] As a fourth aspect of the present invention, there is provided a bone cement comprising powder and liquid, wherein the amount of powder added to a unit volume of liquid is 1.5-2.5 g; Wherein, in terms of mass percentage, the above powder includes: The above-mentioned acrylic acid ester copolymer 69.5-89.99%, Developer 10-30%, Benzoyl peroxide 0.01-0.5%; In terms of mass percentage, the above liquids include: Acrylate monomers 94.5-99.98%, N,N-dimethyl-p-toluidine 0.01-5%, Inhibitor 0.01-0.5%.
[0034] In the embodiment of the present invention, polymethyl methacrylate bone cement is a biomaterial used to fill the gap between bone and implant or bone cavity and has self-setting properties. It is increasingly popular in minimally invasive surgery, but currently acrylate bone cement cannot meet the requirements of mechanical properties of different parts of the human body. Therefore, the present invention proposes a new type of bone cement composed of acrylate copolymers with different glass transition temperatures as powders and liquids, wherein the acrylate copolymers with different glass transition temperatures make the obtained bone cement have different strengths and toughness, which can be adapted to different parts of the human body.
[0035] According to an embodiment of the present invention, the acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In addition to the above-mentioned acrylate monomers, other acrylate monomers that can be used for medical treatment that are not mentioned can also be used.
[0036] According to an embodiment of the present invention, the developer includes at least one of barium sulfate, zirconium dioxide, iopamidol, iohexol, sodium diatrizoate, and metallic tantalum. Adding the developer can enhance the visibility of bone cement in medical images (such as X-rays, CT, etc.).
[0037] According to an embodiment of the present invention, the polymerization inhibitor includes at least one of hydroquinone, p-benzoquinone, and 1,1-diphenyl-2-trinitrophenylhydrazine. The main function of adding the polymerization inhibitor to the bone cement is to prevent the premature polymerization of the acrylate monomer during the mixing and curing process, to ensure that the bone cement maintains plasticity and fluidity during use, and to facilitate surgical operation.
[0038] According to an embodiment of the present invention, optionally, bone cement further comprises at least one of osteoporosis treatment drugs, antibiotics, compatibility additives, adjuvants, and pigments. Preferably, osteoporosis treatment drugs include at least one of bisphosphonates, denosumab, romozumab, parathyroid hormone, and vitamins, wherein bisphosphonates include alendronate, neridronate, and ibandronate, and vitamins include vitamin D and vitamin K; antibiotics include at least one of gentamicin and vancomycin; compatibility additives include at least one of hydroxyapatite, tricalcium phosphate, calcium sulfate, dicalcium silicate, and tricalcium silicate; adjuvants include bioglass; and pigments include at least one of chlorophyll pigments and carotene pigments. Among them, antibiotics play a role in preventing inflammation; compatibility additives can enhance the biocompatibility of bone cement; adjuvants can be used to enhance the mechanical properties of bone filling materials; pigments are added to bone cement so that there is a significant contrast effect during surgery, which helps doctors clearly identify the location and distribution of bone filling materials in the surgical area.
[0039] As a fifth aspect of the present invention, there is provided a method for preparing the above-mentioned bone cement, comprising: The acrylic copolymer, developer and benzoyl peroxide are mixed to obtain bone cement powder; Mixing acrylate monomers, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain liquid bone cement; adding the powder into the liquid and mixing to obtain bone cement; Among them, the amount of powder added per unit volume of liquid is 1.5-2.5g.
[0040] In an embodiment of the present invention, the powder raw material and the liquid raw material are mixed separately and set aside. When used, the powder and the liquid are evenly mixed in proportion, and a self-polymerization reaction occurs between the powder and the liquid. After the reaction is completed, bone cements with different strengths and moduli can be obtained. The preparation method is simple, takes a short time, and can be applied to different parts of the human body or other commercial applications.
[0041] As a sixth aspect of the present invention, there is provided an application of the above-mentioned bone cement, comprising at least one of the following: Application in the treatment of osteoporotic fractures; Application in the fixation material of prosthesis in joint replacement.
[0042] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.
[0043] Example 1
[0044] In this Example 1, a methyl methacrylate-2-ethylhexyl acrylate copolymer was prepared. The specific preparation method is as follows.
[0045] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for 3 times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA), 10 mL of 2-ethylhexyl acrylate (EHA) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the reaction was carried out at a constant temperature of 70 ° C with nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C for aging for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was washed with hydrochloric acid to remove the dispersant, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate-2-ethylhexyl acrylate copolymer was obtained by sieving.
[0046] Example 2
[0047] In this Example 2, methyl methacrylate-styrene copolymer was prepared, and the specific preparation method is as follows.
[0048] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for 3 times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA), 6 mL of styrene (St) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the reaction was carried out at a constant temperature of 70 ° C with nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C for aging for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was washed with hydrochloric acid to remove the dispersant, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate-styrene copolymer was obtained by sieving.
[0049] Example 3
[0050] In this Example 3, a methyl methacrylate-ethyl methacrylate copolymer was prepared. The specific preparation method is as follows.
[0051] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for 3 times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA), 10 mL of ethyl methacrylate (EMA) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the reaction was carried out at a constant temperature of 70 ° C with nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C and matured for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was washed with hydrochloric acid to remove the dispersant, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate-ethyl methacrylate copolymer was obtained by sieving.
[0052] Example 4
[0053] In this Example 4, a methyl methacrylate-methyl acrylate copolymer was prepared. The specific preparation method is as follows.
[0054] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for three times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA), 10 mL of methyl acrylate (MA) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the reaction was carried out at a constant temperature of 70 ° C with nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C for aging for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was removed by washing with hydrochloric acid, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate-methyl acrylate copolymer was obtained by sieving.
[0055] Example 5
[0056] In this Example 5, methyl methacrylate-1,3-divinyltetramethyldisiloxane copolymer was prepared, and the specific preparation method was as follows.
[0057] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for 3 times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA), 10 mL of 1,3-divinyltetramethyldisiloxane (DTMS) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the temperature was kept at 70 ° C for nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C for aging for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was washed with hydrochloric acid to remove the dispersant, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate-1,3-divinyltetramethyldisiloxane copolymer was obtained by sieving.
[0058] Comparative Example 1
[0059] In this comparative example 1, methyl methacrylate homopolymer was prepared, and the specific preparation method is as follows.
[0060] First, the methacrylate was extracted by a separatory funnel, washed with a 5% sodium hydroxide aqueous solution for 3 times, then washed with water until neutral, and dried with calcium chloride to remove the inhibitor in commercial methyl methacrylate. Then, 1.5 g of polyvinyl alcohol dispersant was added to 180 mL of deionized water, the water bath temperature was kept at 70 ° C, and the timed stirring was 0.5 h to activate the dispersant to obtain a dispersant aqueous solution. 20 mL of methyl methacrylate (MMA) and 1.0 g of benzoyl peroxide were added to the dispersant aqueous solution, the stirring speed was 800 rpm / min, and the temperature was kept at 70 ° C for nitrogen protection for 1 h. After the reaction was completed, the temperature was raised to 90 ° C for aging for 2 h to terminate the reaction. After standing and settling, the supernatant was removed, the dispersant was washed with hydrochloric acid to remove the dispersant, and a large amount of distilled water was used to wash until neutral. After filtration, vacuum drying was performed, and the product methyl methacrylate homopolymer was obtained by sieving.
[0061] Furthermore, the prepared different acrylic copolymers were tested for glass transition temperatures using a differential scanning calorimeter. The test results are shown in Table 1.
[0062] Table 1 Glass transition temperature of different acrylic copolymers
[0063] As can be seen from Table 1, acrylic copolymers with different glass transition temperatures can be obtained by adding different monomers. Different glass transition temperatures lead to different strengths and toughness, thereby meeting the needs of different medical scenarios.
[0064] Furthermore, the prepared different acrylic copolymers were mixed with MMA liquid in proportion, stirred for 1-2 minutes, and then poured into a fixed mold with a length of 75 mm, a width of 10 mm, and a thickness of 3.3 mm to perform mechanical property tests of flexural strength and flexural modulus. According to the method described in ISO 5833:2002 "Surgical Implants - Acrylic Resin Bone Cement", the mechanical property indicators of the acrylic copolymers in the above embodiments and comparative examples were tested, and the test results are shown in Table 2.
[0065] Table 2 Mechanical properties test results of different acrylic copolymers
[0066] As can be seen from Table 2, the flexural strength and flexural modulus of the acrylic copolymers obtained by adding different monomers are significantly changed compared with those of pure methyl methacrylate homopolymer, among which the flexural modulus (i.e., stiffness) of the acrylic copolymers with styrene added is significantly increased compared with that of pure methyl methacrylate homopolymer, and the flexural strength and flexural modulus of the other acrylic copolymers with different monomers added are reduced to varying degrees compared with those of pure methyl methacrylate homopolymer.
[0067] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An acrylic copolymer having different glass transition temperatures, wherein: The acrylic copolymer is obtained by copolymerizing methyl methacrylate or its homopolymer and an organic monomer or its homopolymer; Wherein, the organic monomer or its homopolymer includes one or two of styrene, polystyrene, methyl acrylate, polymethyl acrylate, ethyl methacrylate, polyethyl methacrylate, 2-ethylhexyl acrylate, poly2-ethylhexyl acrylate, and organosiloxane; The glass transition temperature of the acrylic copolymer is -60 to 140°C.
2. A method for preparing the acrylic acid ester copolymer according to claim 1, comprising: Methyl methacrylate or its homopolymer and organic monomer or its homopolymer are added to a dispersant aqueous solution, and an initiator is added to perform a polymerization reaction in an inert gas under heating, and then a aging reaction is performed to obtain an acrylic ester copolymer.
3. The preparation method according to claim 2, wherein The dispersant includes at least one of polyvinyl alcohol, tricalcium phosphate, and hydroxy calcium phosphate; The initiator includes any one of azobisisobutyronitrile, benzoyl peroxide, and ammonium persulfate.
4. The preparation method according to claim 2, wherein The polymerization reaction temperature is 60-80°C, and the polymerization reaction time is 0.5-3.5h; The temperature of the aging reaction is 80-100° C., and the time of the aging reaction is 1-3 hours.
5. The preparation method according to claim 2, wherein: The mass ratio of the methyl methacrylate or its homopolymer to the organic monomer or its homopolymer is 1-9:1; The mass ratio of the total mass of the methyl methacrylate or its homopolymer and the organic monomer or its homopolymer to the dispersant aqueous solution is 1:19 to 3:7; The concentration of the dispersant is 0.005-0.02 g / mL; The mass of the initiator is 1-10 wt % of the total mass of the methyl methacrylate or its homopolymer and the organic monomer or its homopolymer.
6. An application of the acrylic acid ester copolymer as claimed in claim 1, wherein: The application includes at least one of the following: Application in the preparation of bone cement for treating osteoporotic fractures; Use of bone cement as a fixation for prostheses in joint replacement surgery; Application as orthodontic base or denture base in dental treatment; Application as dental model in dental treatment; In the field of medical aesthetics, it is used as a filler for plastic surgery or repair.
7. A bone cement, wherein: The bone cement comprises powder and liquid, and the amount of the powder added per unit volume of the liquid is 1.5-2.5 g; Wherein, in terms of mass percentage, the powder comprises: 69.5-89.99% of the acrylic copolymer according to claim 1, Developer 10-30%, Benzoyl peroxide 0.01-0.5%; In terms of mass percentage, the liquid comprises: Acrylate monomers 94.5-99.98%, N,N-dimethyl-p-toluidine 0.01-5%, Inhibitor 0.01-0.5%.
8. The bone cement according to claim 7, wherein: The acrylic acid ester monomers include at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; The developer comprises at least one of barium sulfate, zirconium dioxide, iopamidol, iohexol, sodium diatrizoate, and metal tantalum; The polymerization inhibitor includes at least one of hydroquinone, p-benzoquinone, and 1,1-diphenyl-2-trinitrophenylhydrazine; and Optionally, the bone cement further comprises at least one of osteoporosis treatment drugs, antibiotics, compatibility additives, adjuvants, and pigments; Preferably, the osteoporosis treatment drug includes at least one of bisphosphonates, denosumab, romosuzumab, parathyroid hormone, and vitamins; The antibiotics include at least one of gentamicin and vancomycin; The compatibility additive includes at least one of hydroxyapatite, tricalcium phosphate, calcium sulfate, dicalcium silicate, and tricalcium silicate; The auxiliary agent includes bioglass; The pigment includes at least one of chlorophyll pigments and carotene pigments.
9. A method for preparing bone cement as claimed in claim 7, comprising: Mixing the acrylic copolymer as claimed in claim 1, a developer, and benzoyl peroxide to obtain a powder of bone cement; Mixing acrylate monomers, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain liquid bone cement; Adding the powder into the liquid and mixing them to obtain the bone cement; Wherein, the added amount of the powder is 1.5-2.5g per unit volume of the liquid.
10. A use of the bone cement as claimed in claim 7, wherein: The application includes at least one of the following: Application in the treatment of osteoporotic fractures; Application in fixation materials of prostheses in joint replacement surgery.
Citation Information
Patent Citations
Low-temperature injectable acrylic resin bone cement and preparation method thereof
CN106729974A
Silicone modified acrylic resin and application
CN111533854A
Thermoplastic acrylate emulsion, preparation method and application thereof
CN112126003A
Bone cement composition
US20040157954A1
Bone cement
US5276070A
